Centrosome clustering and chromosomal (in)stability: A matter of life and death - Krämer, Alwin; Maier, Bettina; Bartek, Jiri (Molecular oncology, 2011)
Centrosome abnormalities occur commonly in cancer, and contribute to chromosomal instability and tumorigenesis. New evidence on a phylogenetically conserved mechanism termed ‘centrosomal clustering’ provides exciting insights into how cells with supernumerary centrosomes adapt to avoid lethal multipolar divisions. Here, we highlight the emerging molecular basis of centrosome clustering, and its impact on asymmetric divisions of stem cells, chromosomal (in)stability and malignant transformation. Finally, pharmacological inhibition of centrosome clustering promises to selectively target tumor cells.
Gesehen am 08.07.2022